A CASE OF THANATOPHORIC DYSPLASIA TYPE I: THE FIRST CLINICOPATHOLOGIC REPORT FROM ETHIOPIA - Dereje, Bethel; Gebrehiwot, Yirgu; Schenider, Jakob (Ethiopian Journal of Reproductive Health, 2018)
ABSTRACT Thanatophoric dysplasia (TD) is a short-limb neonatal dwarfism syndrome that is usually lethal in the perinatal period1. It is characterized by markedly underdeveloped skeleton and short-limb dwarfism. TD is caused by a mutation of the fibroblast growth factor receptor 3 gene (FGFR3), which is located on the short arm of chromosome 42,3.This study reports a neonate born at Tikur Anbessa Teaching Hospital with features of thanatophoric dysplasia which was proven radiologically and pathomorphologically. The mother presented to the hospital at 39 +1 weeks of gestational age with ultrasound diagnosis of achondroplasia. She developed cephalopelvic disproportion and underwent caesarian section. Outcome was an alive anomalous female neonate with a weight of 2900 gms of 4, 2, 2 & 0 in the 1st, 5th, 10th & 20th minute APGAR scores, respectively. The neonate expired due to severe respiratory distress despite resuscitation. The parturient died following pulmonary thromboembolism diagnosed on her second postoperative day. CONCLUSION: Thanatophoric dysplasia is a lethal skeletal anomaly which should be diagnosed and managed in the second trimester of pregnancy. Missing this case in the mid-trimester costed note only the physical, psychological and the economic burden but also the life of the mother. KEY WORDS: Thanatophoric dysplasia, fibroblast growth factor receptor 3 gene (FGFR3) (Ethiopian Journal of Reproductive Health 2018; 10; 3: 65-70)